PENGARUH TERAPI NYANYIAN (CHANTING) MANTRA OM TERHADAP TINGKAT KECEMASAN PASIEN KANKER YANG AKAN DILAKUKAN KEMOTERAPI STUDI DILAKUKAN DI RUANG ANGSOKA 2 RSUP SANGLAH DENPASAR - Ni Luh Gede Lily Permata Sari; Dewa Gede Anom; Made Surata Witarsa (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
Cancer is a disease caused by abnormality of cell growth. Chemotherapy is one of the therapies that used to treat cancer, but have some side effects. Anxiety is a negative effect of chemotherapy. Singing (chanting) mantra om therapy is a non-pharmacological therapy which can treat anxiety. This therapy is performed by repeatedly singing the mantra om then causing a relaxing effect and decrease levels of anxiety. This study aims to determine the effect of singing (chanting) mantra om therapy in patients who will be performed chemotherapy. This study used the pre-experimental method with One group pre-test and post-test design. The samples consisted of 23 people were selected by consecutive sampling and include in inclusion and exclusion criteria. Anxiety levels were measured by BAI questionnaire and analyzed by univariate and bivariate techniques. This theraphy did in 30 minutes. This study was conducted at room Angsoka 2 of Sanglah Hospital on 8 May-21 may 2015. The Results of bivariate analysis by Wilcoxon Sign Rank Test showed p value = 0,000, with a value of ? = 0.05. It indicated there was a significant effect betwen this therapy toward anxiety levels of patients. This therapy can decrease the anxiety levels of patient who will performe chemotherapy. The weakneses of this study are other factors that cause anxiety have not been able controlled thus enabling the existence of bias, performed in a short period of time, and objectivity of respondents in filling out the questionnaire.